Singapore Higher Education and COVID-19: An Early and Measured Response - Ang, Natalie; Stanfield, Dave (International Higher Education, 2020)
By acting early and using a measured response to COVID-19, Singapore was able to keep higher education intact far longer than many countries. The government implemented rigorous contact tracing, social distancing regulations, and isolation strategies that prevented rapid spread. University students, faculty, and staff were required to follow strict temperature taking routines, travel declarations, and the like. With a recent surge in confirmed cases, the authors highlight several uncertainties for the coming academic year in Singapore higher education.